Sediment Yield Modeling and Mapping of the Spatial Distribution of Soil Erosion-Prone Areas - Chala Hailu Sime; Wondmagegn Taye Abebe (Applied and Environmental Soil Science)
Sediment movement is the most critical problem in Ethiopia, notably in the Ketar River watershed, which is located in the Rift Valley Basin. The Ketar River flows through rugged terrain with steep slopes and high sediment movement. The purpose of the study is to evaluate the Soil and Water Assessment Tool's (SWAT) ability to simulate sediment and to identify areas that are vulnerable to soil erosion. This will aid water resource planners in determining the appropriate corrective action. In SWAT sediment sensitivity analysis, the USLE soil erodibility factor (USLE-K) is found to be the most sensitive sediment parameter. The SWAT model sediment simulation performance is evaluated using the coefficient of determination (R2) and Nash-Sutcliffe Efficiency (NSE). The model performance results in R2 and NSE values of 0.69 and 0.55 for calibration and 0.73 and 0.51 for validation, respectively, using the SWAT Calibration and Uncertainty Program (SWAT-CUP). The sediment-prone area subbasins have steep slopes and were mostly covered by cultivated land. Annual sediment yield from cultivated land was approximately 1872.12 t/y, while yield for moderately cultivated grassland was 171.45 t/y. Woodland and forest land have less soil erosion rate. The subbasin highly covered by Eutric Nitisols is found in very high soil erosion-prone areas. Sediment yield from a slight slope is almost zero, whereas sediment yield from steep and very steep slopes is very high. The slope of the subbasin is an important factor in determining sediment yield, followed by land cover and soil types. The very high sediment yield rate area accounted for 39.64% of the total subbasin and it needs soil conservation planning.